An Efficient and General Strategy toward the Synthesis of Polyethylene-Based Cyclic Polymers - Jiang, Yu; Zhang, Zhen; Wang, De; Hadjichristidis, Nikos (Macromolecules, 2018)
A novel strategy toward well-defined polyethylene-based cyclic homo/copolymers is presented. Tris(3-(anthracen-9-ylmethoxy)propyl)borane, prepared by hydroboration of 9-((allyloxy)methyl)anthracene with BH3, was used to initiate the polyhomologation of dimethylsulfoxonium methylide to afford well-defined anthracene-teminated linear polyethylene (PE). The azido and alkynyl groups at α and ω positions of the PE chain were introduced via the anthracene/maleimide Diels–Alder (D–A) reaction and esterification, respectively. Subsequent intramolecular “click” cyclization of the α,ω-heterofunctionalized linear PE gave cyclic PE. Combining this efficient strategy with ring-opening polymerization (ROP), more complex PE-based cyclic block copolymer architectures have been designed and synthesized, such as diblock cyclic and triblock tadpole copolymers. All intermediates and final products were characterized by high-temperature gel permeation chromatography, proton nuclear magnetic resonance spectroscopy, and differential scanning calorimetry. Initial studies on the thermal behavior of the cyclic homo- and block copolymers revealed the big influence of the cyclic structure on the melting temperature and crystallinity as compared to their corresponding precursors.